Genetic Variability and Prediction of T Epitopes of the HPV16 E2 Gene in Asymptomatic Women from Cajamarca, Peru - Bonifacio-Velez de Villa, E. (2025)
Background: The HPV16 E2 gene plays a crucial role in viral replication and oncogene regulation. This study aimed to assess the genetic variability of the E2 gene and to iden tify immunogenic epitopes of the E2 protein. Methods: The E2 gene was amplified and sequenced. T-cell epitope prediction and evaluation were performed using IEDB, NetMHC pan v4.0, NetMHCIIpan v4.1, VaxiJen, ToxNet, and pLM4Alg. Results: Phylogenetic analysis of 47 E2 sequences demonstrated co-circulation of the D (n = 4) and A (n = 43) HPV16 lineages in Cajamarca. Twenty-eight Single Nucleotide Polymorphism (SNPs) were identified in E2, 21 of which were nonsynonymous. Seventeen variations were associ ated with positive Papanicolaou (Pap) test results. Epitope prediction identified 2 MHC class I and 27 MHC class II epitopes classified as potentially antigenic, non-toxic, and non-allergenic, with an overall global population coverage across both MHC classes of 99.78%. Conclusions: The A HPV16 lineage predominated among the women studied. The identified SNPs indicate substantial variability in the E2 gene and a relationship with endocervical lesions. In total, 29 E2-derived T-cell epitopes with immunogenic potential were identified.